A Five-Year strategic financial plan for Metro Rail Store Group, Inc. - Addun, Princess T., Camacho, Atasha Rain F., Gracia, Julliana Mae M., Mendoza, Charles Brian A., Sales, Meryle F. 4 0 16; 5
Introduction: Metro Retail Stores Group, Inc. is a Philippine supermarket, hypermarket, and department store operator. The company's principal goal is to purchase, sell, and exchange products, crafts, and merchandise of all kinds and descriptions. The grocery division of the company operates under two brand names: Metro Grocery and Metro Fresh N Easy. The Metro Fresh N Easy brand name is utilized for smaller supermarkets that serve as neighborhood businesses. Its department shops operate under the Metro Department Store name. The Super Metro name represents the company's hypermarket retail concept. The company's hypermarkets are a combination of its supermarkets and department shops, offering a wide range of essential everyday things; shopmetro.ph, an online platform for both supermarkets and department stores, allows customers to have their shopping delivered to their homes. It contains around 63 outlets with a total net selling area of 260,000 square meters. In 1982, Victor Gaisano and his wife Sally opened the first Gaisano Metro Department Store and Supermarket in Colon, Cebu City. They began the firm with their four children, Margaret, Jack, Edward, and Frank. Gaisano Metro was eventually called Metro Gaisano, which expanded over time into Metro Department Store and Supermarket. Metro is the leading domestic store in Cebu. Much more than the funds that began the firm, the basic principles established by its patriarch serve as the cornerstone for the company, which has grown from a start-up to the current professional organization. As a result of its ambitious growth, Metro now serves major cities outside of Cebu and the Visayas. Metro has built a foothold in Central Luzon, Southern Luzon, the National Capital Region, Calabarzon, and Bicol. Today, Metro Retail outlets Group, Inc. has evolved into corporation that includes various shop formats: Metro Department shop, Metro Supermarket, and Super Metro Hypermarket, and has grown to 60 outlets. Metro's 40-year history has been tumultuous, beginning with Gaisano Metro and progressing to Metro Gaisano and now Metro Retail Stores Group, Inc. And it has all been for the better. Victor Gaisano and his family demonstrated that good products and services can only go so far; a good brand founded on hard effort and trust earns consumer loyalty. The second-generation Gaisano brothers never forget where their parents, Victor and Sally, started. Their enterprises are a monument to hard work and determination, supported by two generations of successful entrepreneurs, including their parents. For some, having strong business sense is a blessing. However, most of the time, excellent business sense is just a long-term vision of better days ahead. And it is precisely what Victor and Sally Gaisano envisioned for Metro.
Financial Plan: (BSBA major in Financial Management) - Pamantasan ng Lungsod ng Maynila, 2024
Keywords: 2 -- 0; 6; 20; 20; 2